Advances in biological agents in the treatment of inflammatory bowel disease - Na LI; Mei YE (Yixue xinzhi zazhi)
Inflammatory bowel disease (IBD) is a chronic and progressive disease which is currently hard to cure. Traditional treatments, such as aminosalicylates, steroids and immunosuppressants, can only alleviate symptoms, but can’t prevent potential inflammation or change the disease progress. The application of biological agents represents a turning point in the treatment of IBD. With the expansion of research, an increasing number of new biological agents and small molecule drugs have entered various stages of clinical development. The chief focus of this review is the mechanisms of action and clinical trial data on emerging biological agents and small molecule drugs for the treatment of IBD.